Study on the New Concept of the Rotors and Supporting Structure Transformation for Non-linear Vibrations Analysis - Jan Kicinski (New Ideas Concerning Science and Technology Vol. 7, 2021)
In this paper we will discuss the problem of mathematical description of two basic sub-systems composing a rotating machine, which are the line of rotors with bearings and the supporting structure. If we want to obtain non-elliptic trajectories, with various types of defects in systems operation and complicated vibration spectra coded in their shapes - which makes the basis for technical diagnostics - we must turn to the non-linear analysis and solve the equations of motion in another reference system. The subsystems that frequently reveal non-linear characteristics include the line of rotors with constructional and operational imperfections (misalignment, shaft cracks), and, undoubtedly, the slide bearings and labyrinth seals. At the same time the supporting structure can be treated with satisfactory accuracy as a subsystem having the linear characteristics. In this situation a key question is how to unite in one system the supporting structure, with its linear characteristics, and the line of rotors and bearings, resting on the supporting structure and definitely representing the non-linear characteristics. Here, such an elegant notation in the form of a complex matrix for the entire machine is not possible any longer. From the mathematical point of view the situation is becoming dramatically more complicated. This assessment mainly depends on the properties of the construction itself, more precisely on the degree of complexity of its modal model, as well on available measurement or simulation data, and possible interaction of those supporting structure elements which can reveal non-linear characteristics. In this paper we will propose solutions to this problem in the form of so-called adequacy intervals of the supporting structure dynamic characteristics, with relevant transformation of those characteristics, and will present a novel concept how to incorporate those characteristics to the rotor line dynamics, based on a so-called weight functions proportional to the vibration spectrum of the supports. The proposed concept can be of extreme value for defining defect-symptom relations, to be used in a new and rapidly developing discipline of science bearing the name of the model based diagnostics.